Leadership of School Principals in Improving The Quality of Teacher Learning - Malika Ayumi; Inom Nasution (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
School principals play a crucial role in improving the quality of teacher instruction and overall educational outcomes. In the context of rapidly evolving educational demands, principals are expected to manage administrative tasks and act as instructional leaders. This study aims to explore the role of principal leadership in enhancing the quality of teacher instruction at Madrasah Nurul Hakim. Using a qualitative ethnographic approach, data were collected through classroom observations, in-depth interviews with the principal, teachers, and students, and documentation analysis. The findings reveal that the principal implements a participatory leadership style that supports continuous supervision, encourages professional development, and fosters teacher involvement in decision-making processes. The principal effectively enhances teacher competence and instructional performance through regular classroom monitoring, academic supervision, and informal reflective discussions. The impact of such leadership extends to students, who demonstrate increased engagement, discipline, and enthusiasm for learning. It is concluded that effective principal leadership significantly contributes to improving teacher professionalism, positively affecting the quality of learning in schools